ИНТЕГРАЦИЯ СЛОВЕСНОЙ, ИГРОВОЙ И ИЗОБРАЗИТЕЛЬНОЙ ДЕЯТЕЛЬНОСТИ В ПРОЦЕССЕ ФОРМИРОВАНИЯ СВЯЗНОЙ РЕЧИ МЛАДШИХ ШКОЛЬНИКОВ - Каллибекова, Г.А.; Рейембаева, А.П. (SCIENCE and SOCIETY, 2025)
The article is devoted to the study of the integration of verbal, play, and visual activities in the process of forming coherent speech in primary school students. The importance of coherent speech as a foundation for the communicative and personal development of primary school students is considered.